Collective Narcissism as a Basis for Nationalism. Issue 1 (5th May 2022) - Federico, Christopher M.; Golec De Zavala, Agnieszka; Bu, Wen
Abstract : Recent work suggests that collective narcissism—an exaggerated, unrealistic belief in an ingroup's greatness that demands constant external validation—is a strong predictor of a variety of political attitudes. In the present study, we use nationally representative panel data from Poland to examine the relationship between national collective narcissism and nationalism, a belief that the national ingroup is superior and should dominate other nations. We first demonstrate that national collective narcissism, nationalism, and mere satisfaction with national ingroup are distinct. In turn, in both cross‐sectional and panel analyses, we find that (1) national collective narcissism is positively related to nationalism, whereas satisfaction with the national ingroup is not; and (2) national collective narcissism is a stronger predictor of nationalism than national ingroup satisfaction is in absolute terms. Our analyses thus provide evidence that nationalism may be rooted in narcissistic exaggeration of the greatness of the national ingroup rather than nonnarcissistic national ingroup satisfaction.